2015
DOI: 10.1177/1941874415569069
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran-Associated Intracranial Hemorrhage

Abstract: Dabigatran etexilate is an oral direct thrombin inhibitor approved for prevention of stroke and systemic embolization in patients with nonvalvular atrial fibrillation and for the treatment of venous thromboembolism. Although dabigatran has a favorable safety profile, predictable pharmacokinetics, fewer drug interactions than warfarin, and does not require monitoring, clinical data regarding dabigatran reversal are limited. In addition, currently available laboratory assays allow measurement of the presence, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…This trial also supports uninterrupted intraprocedural anticoagulation as an alternative to bridging heparin therapy [67]. WOEST (What is the Optimal anti-platElet and anticoagulant therapy in patients with oral anticoagulation and coronary StenTing) uncovered reduction of bleeding risks and overall mortality with the same thrombotic rate in DAPT with warfarin and clopidogrel, compared to triple anti-thrombotic therapy [67,72].…”
Section: Afcas (Prospective Multi-center Registry Of Patients With Atmentioning
confidence: 58%
See 2 more Smart Citations
“…This trial also supports uninterrupted intraprocedural anticoagulation as an alternative to bridging heparin therapy [67]. WOEST (What is the Optimal anti-platElet and anticoagulant therapy in patients with oral anticoagulation and coronary StenTing) uncovered reduction of bleeding risks and overall mortality with the same thrombotic rate in DAPT with warfarin and clopidogrel, compared to triple anti-thrombotic therapy [67,72].…”
Section: Afcas (Prospective Multi-center Registry Of Patients With Atmentioning
confidence: 58%
“…Apixaban also proved to be unprofitable in trials APPRAISE (Apixaban for Prevention of Acute Ischemic Events) and APPRAISE-2 and it has also been demonstrated that the concomitant use of anti-platelet drugs with these agents increases risk without benefit. ATLAS ACS 2-TIMI 46 and 52 investigated reduced doses of rivaroxaban and revealed its association with lower ischemic and bleeding risks, as well as a decrease in both stent thrombosis and mortality rates; therefore suggesting rivaroxaban to be a potential choice for anticoagulation in triple therapy in the future [68,[70][71][72].…”
Section: Stroke Prevention In Acute Coronary Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…P-gp inhibitors increase dabigatran bioavailability by ~10% to 20% [ 71 ]. There are also case reports of major bleeding in elderly patients taking concomitant dabigatran with P-gp inhibitors that might have been due in part to the inhibition of P-gp, in addition to other factors such as age and decreased renal function [ 72 , 73 ] (Table 1 ). More recently, in a retrospective cohort study of AF patients on dabigatran, concomitant use of digoxin, which is a substrate of P-gp, was associated with 33% increased risk of gastrointestinal bleeding (Table 1 ) [ 74 ].…”
Section: Oral Anticoagulantsmentioning
confidence: 99%